2019
DOI: 10.1109/access.2019.2948879
|View full text |Cite
|
Sign up to set email alerts
|

A Tele-Operated Display With a Predictive Display Algorithm

Abstract: Tele-operated display systems with head mounted displays (HMD) are becoming popular as visual feedback systems for tele-operation systems. However, the users are suffered from time-varying bidirectional delays caused by the latency and limited bandwidth of wireless communication networks. Here, we develop a tele-operated display system and a predictive display algorithm allowing comfortable use of HMDs by operators of tele-operation systems. Inspired by the kinematic model of the human headneck complex, we bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The proposed system, as will be discussed in Section 5.3, attains a high level of usability and is easy to be trained. In comparison with previous works which adopted purely direct control approaches, such as Orosco et al (2021), Madder et al (2020) and Jung et al (2019), we find that these approaches still require highly trained operators and cannot present solutions to avoid high concentration levels and cognitive stresses. It requires the operator’s undivided attention throughout the task working time which increases stress, especially when working in unstructured environments.…”
Section: Related Workmentioning
confidence: 59%
See 1 more Smart Citation
“…The proposed system, as will be discussed in Section 5.3, attains a high level of usability and is easy to be trained. In comparison with previous works which adopted purely direct control approaches, such as Orosco et al (2021), Madder et al (2020) and Jung et al (2019), we find that these approaches still require highly trained operators and cannot present solutions to avoid high concentration levels and cognitive stresses. It requires the operator’s undivided attention throughout the task working time which increases stress, especially when working in unstructured environments.…”
Section: Related Workmentioning
confidence: 59%
“…They found that, in comparison to previous approaches that included sparse multivariate linear regression, remote system control is improved when the time delay is known ahead of time. Jung et al (2019) used a kinematic model of the human head and neck, as well as camera parameters, to create a predictive display. The authors used a simple linear model of motion to predict future images based on current images using the relationship between camera orientation and the positional changes of the human controllers.…”
Section: Related Workmentioning
confidence: 99%
“…They use a first-order gaze movement model with a time delay to predict specific target points and use these as points of movement during the time delay. Jung et al ( 2019 ) utilize a predictive display using a kinematic model of the human head and neck along with camera parameters. This is an interesting approach where they use the relationship between camera orientation and the human controllers' positional changes to predict future images based on current images using a simple linear model of motion.…”
Section: Time Series Prediction Methods For Mitigating Time Delay mentioning
confidence: 99%